The missing link: how the holobiont concept provides a genetic framework for rapid evolution and the inheritance of acquired characteristics - Huitzil, Saúl; Huepe, Cristián; Aldana, Maximino; Frank, Alejandro (Frontiers in Ecology and Evolution, 2023)
The microbiome, encompassing the genetic material of all the microorganisms associated with a host organism, has an evolutionary potential that has been overlooked in the prevailing paradigm of the Modern Synthesis. Recognizing this untapped potential could shed light on various unresolved evolutionary phenomena that have remained elusive through the lens of genetic variants alone. Such phenomena include rapid evolution, inheritance of acquired characteristics, and the missing heritability problem. In this review, we explore the microbiome's potential role in these processes, considering the holistic holobiont perspective as a possible guiding framework for new insights. Drawing inspiration from the foundational contributions of Rosenberg, Zilber-Rosenberg, and their contemporaries, we emphasize the significance of the microbiome in driving evolutionary innovation. Building on our previous research, coupled with emerging studies highlighting the microbiome's relevance in addressing missing heritability, we advocate for its 1 Huitzil et al.recognition as a wellspring of evolutionary innovation. Throughout, we collate and analyze recent evidence to bolster our position and delve into the broader implications of these findings.